ISOTOPIC INVESTIGATION OF GROUNDWATER RECHARGE MECHANISM IN THAL DOAB - Akram, W.; Latif, Z.; Iqbal, N.; Tasneem, M. A. (The Nucleus, 2014)
Isotope techniques were applied in a selected area of Punjab known as Thal Doab for investigating origin, recharge and age/residence time of groundwater. Surface water and groundwater samples were collected from 211 sampling points spread over the entire study area. The sampling points included rivers/canals representing the surface water, hand pumps representing shallow groundwater and tube wells representing deep groundwater. Rain samples were also collected at Chashma. The collected samples were analyzed for environmental isotopes (2H, 3H, 18O). Isotopic data of recharge sources indicated that rivers/canals and rainfall have quite different signatures. Data of groundwater clearly demonstrated spatial variation of isotopic composition illustrating recharge from different sources and in varying proportions. Rain appears to be the main source of recharge in upper eastern part of the doab. Rest of the area is mainly recharged by surface water. 18O values of shallow and deep groundwater showed similar geographical distribution proving that they are interconnected and have same recharge mechanism. Groundwater has different age/residence time in various zones ranging from fresh to more than 50 years.